Sexual well-being among older adults in China (SWELL): protocol for a multicenter cross-sectional study. Issue 1 (30th January 2023) - Wang, Bingyi; Peng, Xin; Liang, Bowen; Fu, Leiwen; Tian, Tian; Liu, Jiewei; Li, Yuwei; Li, Xinyi; Wang, Shihao; Zheng, Weiran; Xiao, Xin; Shi, Tongxin; et al.
Abstract : Introduction: Existing studies on sexual health generally focus on younger populations, while the sexual well-being of older adults has received insufficient attention. This protocol describes the design of a study on sexual well-being and its correlates among older adults in China. Methods and analysis: We present the protocol for a multicentre observational study to investigate sexual well-being among Chinese older adults (SWELL). Eligible participants are men and women aged 50 years and older from East, West, South and North China, including older adults living in the community and older adults living with HIV. A multistage sampling approach is used in the SWELL Study. We will collect a questionnaire about sexual health (sexual knowledge, sexual attitude, sexual behaviours, sexually transmitted infections, etc). Blood specimens will be tested for sex hormones (estradiol for women, testosterone for men), biochemical items (eg, cholesterol, triglycerides, low-density lipoprotein, high-density lipoprotein, urea, creatinine and uric acid) and syphilis (determined by toluidine red unheated serum test and Treponema pallidum particle agglutination test). The primary analysis will elucidate the current status of sexual health among older adults in China and its correlates. Secondary analyses will compare sexual well-being among older adults in four regions across China. Approximately 3540 older adults will be recruited into the SWELL Study. Ethics and dissemination: This study was approved by the Human Research Ethics Committee of the School of Public Health (Shenzhen), Sun Yat-sen University (approval number SYSU-PHS[2019]006). Verbal informed consent will be obtained from all participants before any study procedure. Data will be anonymised, and participants will not be identified through any data, transcripts or publications. Findings from the SWELL Study will be disseminated widely through peer-reviewed scientific journals and at national and international conferences.